ANALISIS DAYASAING UBI JALAR CILEMBU DI KABUPATEN SUMEDANG JAWA BARAT - Ana Hoeridah; Tintin Sarianti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2011)
Today, Indonesia is still export fresh agriculture product with low selling price and competitive power than processed product with higher selling price. The condition also observed for sweet potato that exported in the fresh form with low selling price and in turn lowering the competitive power of this product. Province of West Java is one of sweet potato production center. In 2009, “Cilembu” sweet potato becomes leading product of this commodity group that mostly produced in Subang Regency. Market destination of “Cilembu” is not only for domestic demand but also exported to many destination countries including Japan, Malaysia, Vietnam, Hongkong, and Singapore, but selling in the fresh form. Due to the large potential, it is important to examine the competitive power of the commodity and effect of government policy on “Cilembu” farming in Subang Regency. The research study was selected on purposive basis. The data analyzed using Policy Analysis Matrix (PAM) and sensitivity analysis. The result indicated that “Cilembu” farming in Sumedang Regency is profitable both financial and economic and has good competitive power (either comparative or competitive advantage). Government policy on domestic input is not effective yet because producer must pay higher price on the input than it should be. The policy is effective for tradable input due to subsidy. Output policy has restrictive nature due to export taxes and no subsidy for the commodity. Sensitivity analysis show that increasing of labor wage and changing on exchange rate is not affect competitive and comparative advantage, while decreasing on output will affect on competitive advantage (comparative advantage still exist).